Transcriptional analysis of the gap-pgk-tpi-ppc gene cluster of Corynebacterium glutamicum. - Schwinde, J W (1993)
The transcriptional organization of the Corynebacterium glutamicum gap-pgk-tpi-ppc gene cluster, encoding glyceraldehyde-3-phosphate dehydrogenase, 3-phosphoglycerate kinase, triosephosphate isomerase, and phosphoenolpyruvate carboxylase, was investigated by Northern (RNA) blot and primer extension analyses. Four transcripts corresponding to gap, to gap-pgk-tpi, to pgk-tpi, and to pgk-tpi-ppc were identified. The respective transcriptional initiation sites in front of gap and pgk were located, and, from the analysis of DNA sequences upstream of these and of previously determined transcriptional start sites, common structures which may be important for promoter function in C. glutamicum are discussed.